Морожены волки: сказки / Степан Писахов ; рисовала Елена Базанова - Писахов Степан Григорьевич (Речь, 2015)
Экземпляры: ф.1 (20220125) / Инвентарный номер: 61571 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: П 34 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6-4